Pengaruh Kualitas Pelayanan, Varian Produk, Harga Terhadap Keputusan Pembelian Pada Kewirausahaan Santri Pesantren Kampus Ainul Yaqin - Shofi Mustajibullah; Nur Hidayati; Abdullah Syakur Novianto (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract Islamic boarding schools have business units that are managed independently, one of which is Entrepreneurship at the Ainul Yaqin Campus Islamic Boarding School which is based at the Ainul Yaqin Campus Islamic Boarding School. This research is based on the phenomenon of transactions that occur in Islamic Boarding School Entrepreneurship, Ainul Yaqin Campus. In fact, in carrying out its operations the Entrepreneurship of the Ainul Yaqin Campus Islamic Boarding School still ignores important variables or aspects of the economy. Because of this, the variables in this study are Service Quality, Product Variants and Prices with consideration of their influence on the Purchasing Decisions of the students at the Entrepreneurship Islamic Boarding School, Ainul Yaqin Campus. The samples taken in this study were 85 people using the malhotra formula, in the form of Islamic boarding school students, Ainul Yaqin Campus. In the implementation of this research using multiple linear regression analysis method with stone tools, namely SPSS. In the end, simultaneously, all independent variables affect the dependent variable. Partially, both Service Quality, Product Variants, Prices affect Purchase Decisions. Keywords: Service Quality, Product Variant, Price, Purchase Decision